4 - Gender, Globalisation and Marginalisation in Africa: 10.4314/ad.v28i2.22177 - Lai Olurode, (Africa Development, 2022)
Globalisation is discussed as an all-encompassing historical process of change that has been with humanity for generations. Yet, it is a system of domination and disempowerment which impacts social groups differently and some detri mentally. Globalisation is altering gender relations in societies as well as dis tancing people from the very cultural resources within their societies. In the latter sense, globalisation deepens dependency in all its facets. The paper's main objective is to demonstrate how globalisation is producing marginalisation be tween gender groups. In its recent ramification, globalisation is portrayed as liberalisation of the economy (structural adjustment programmes) and of poli tics (démocratisation). But men and women differ in their responses to globalisation and in the strategies that are being employed to smuggle gender specific agendas into the state arena. As its methodology, the paper employs content analysis, observation, and personal interview to enrich the analysis. The paper, in its conçlusion, cautions against an undiscriminatory consumption of the products (whether material or immaterial) of globalisation. It also describes the forms of resistance women have deployed in the face of globalisation.